Doppler echocardiographic study in adolescents and young adults with sickle cell anemia - Martins,Wolney de Andrade (1999)
OBJECTIVE: Anatomical and functional assessment of the heart through Doppler and echocardiography in patients with cell anemia (SCA). METHODS: Twenty-five patients with SCA and ages ranging from 14 to 45 years were prospectively studied in a comparison with 25 healthy volunteers. All of them underwent clinical and laboratory evaluation and Doppler echocardiography as well.The measurements were converted into body surface indices. RESULTS: There were increases in all chamber diameters and left ventricle (LV) mass of the SCA patients. It was characterised an eccentric hypertrophy of the left ventricle. The preload was increased (left ventricle end-diastolic volume) and the afterload was decreased (diastolic blood pressure, peripheral vascular resistance and end-systolic parietal stress ESPS). The cardiac index was increased due to the stroke volume. The ejection fraction and the percentage of the systolic shortening , as well as the systolic time intervals of the LV were equivalent. The isovolumetric contraction period of the LV was increased. The mitral E-septum distance and the end-systolic volume index (ESVi) were increased. The ESPS/ESVi ratio,a loading independent parameter, was decreased in SCA, suggesting systolic dysfunction. No significant differences in the diastolic function or in the pulmonary pressure occurred. CONCLUSION: Chamber dilations, eccentric hypertrophy and systolic dysfunction confirm the evidence of the literature in characterizing a sickle cell anemia cardiomyopathy.